Mandatory lane-changing modelling based on a game theoretic approach in traditional and connected environments. Issue 1 (13th January 2023) - Cheng, Guozhu; Sun, Qiuyue; Bie, Yiming
Abstract: The paper proposes a model of mandatory lane-changing behaviour based on a non-cooperative game in a traditional environment and analyses its applicability in a connected environment. In order to solve the problem of traffic safety and traffic congestion caused by mandatory lane-changing on urban roads, this paper applies the non-cooperative game theory to describe the game behaviour of the two parties, the lane-changing vehicle and the vehicle behind the target lane, in the connected and traditional environments respectively, and constructs the model considering the safety gain, speed gain and lane-changing gain to obtain a game model and the Nash equilibrium solution. The model is calibrated and tested using NGSIM data, and the results of the study show that the model has a good performance for the decision behaviour of lane-changing vehicles and lag vehicles for mandatory lane-changing behaviour on urban roads.